Natural Enemy Complex at the Nursery Stage of Albizia procera (Roxb.) Benth. and A. Lebbek (L.) Benth. in Punjab - Pandha, Y. S.; Saini, M. S.; Dargan, J. S. (Indian Forester, 2007)
It was explored that Coccinellids viz. Coccinella septumpunctata, Menochilus sexmaculatus and Spiders viz. Oxyopes pandae, Araneus nauticus and Zygoballus sp. and Preying mantis Creobrator pictipennis constitutes major natural enemies on insect pests of A. lebbek and A. procera. Predation by Pentatomid , Canthecona furcellata was more common among seedlings of A. procera.